2022
DOI: 10.21608/zumj.2022.153039.2610
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal development of the rat cerebellar granule cells following maternal administration of thyme and tramadol

Abstract: Introduction: Tramadol abuse is increasing among male and female teenagers with a history of substance abuse and anxiety. Many adolescent addicts take tramadol as substitute for other narcotics. Tramadol uptake is associated with many side effects. Thyme has been presumed to have a neuroprotective effect against brain damage. Aim of the work:To assess the harmful effects of tramadol on the pre and postnatal development of the rat cerebellar granule cells and to evaluate the possible ameliorative effect of thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Recent research work has demonstrated that the use of tramadol during pregnancy and lactation have detrimental effects on neuronal development, synapse formation and survival in the cerebrum and cerebellum of the developing progeny (Allen et al 2021). The potential hazards of tramadol on the cerebellum and the function of opioid receptors in the cerebellum have been depicted in a relatively consistent manner by accumulating evidence (Mohamed et al 2022). Tramadol has been documented to cause disruptions in the metabolism of various amino acids that are involved in regulating the neuropathophysiology of the cerebellum and to in uence the activity of several essential enzymes in the cerebellum.…”
Section: Introductionmentioning
confidence: 94%
“…Recent research work has demonstrated that the use of tramadol during pregnancy and lactation have detrimental effects on neuronal development, synapse formation and survival in the cerebrum and cerebellum of the developing progeny (Allen et al 2021). The potential hazards of tramadol on the cerebellum and the function of opioid receptors in the cerebellum have been depicted in a relatively consistent manner by accumulating evidence (Mohamed et al 2022). Tramadol has been documented to cause disruptions in the metabolism of various amino acids that are involved in regulating the neuropathophysiology of the cerebellum and to in uence the activity of several essential enzymes in the cerebellum.…”
Section: Introductionmentioning
confidence: 94%